Identification of new anti-mycobacterial agents based on quinoline-isatin hybrids targeting enoyl acyl carrier protein reductase (InhA) - Khaleel, Eman F; Sabt, Ahmed; Korycka-Machala, Malgorzata; Badi, Rehab Mustafa; Son, Ninh The; Ha, Nguyen Xuan; Hamissa, Mohamed Farouk; Elsawi, Ahmed E; Elkaeed, Eslam B; Dziadek, Bozena; Eldehna, Wagdy M; Dziadek, Jaroslaw (Bioorganic chemistry, 2024)
Tuberculosis (TB) is a global issue that poses a significant economic burden as a result of the ongoing emergence of drug-resistant strains. The urgent requirement for the development of novel antitubercular drugs can be addressed by targeting specific enzymes. One such enzyme, Mycobacterium tuberculosis (MTB) enoyl-acyl carrier protein (enoyl-ACP) reductase (InhA), plays a crucial role in the survival of the MTB bacterium. In this research study, a series of hybrid compounds combining quinolone and isatin were synthesized and assessed for their effectiveness against MTB, as well as their ability to inhibit the activity of the InhA enzyme in this bacterium. Among the compounds tested, 7a and 5g exhibited the most potent inhibitory activity against MTB, with minimum inhibitory concentration (MIC) values of 55 and 62.5 μg/mL, respectively. These compounds were further evaluated for their inhibitory effects on InhA and demonstrated significant activity compared to the reference drug Isoniazid (INH), with IC50 values of 0.35 ± 0.01 and 1.56 ± 0.06 μM, respectively. Molecular docking studies investigated the interactions between compounds 7a and 5g and the target enzyme, revealing hydrophobic contacts with important amino acid residues in the active site. To further confirm the stability of the complexes formed by 5g and 7a with the target enzyme, molecular dynamic simulations were employed, which demonstrated that both compounds 7a and 5g undergo minor structural changes and remain nearly stable throughout the simulated process, as assessed through RMSD, RMSF, and Rg values.
Keywords: Quinolines; Mycobacterium tuberculosis; antituberkulotika; mikrobiální testy citlivosti; simulace molekulového dockingu; Isatin; bakteriální proteiny; Bacterial Proteins; chinoliny; lidé; Microbial Sensitivity Tests; Oxidoreductases; oxidoreduktasy; Acyl Carrier Protein; Antitubercular Agents; isatin; protein přenášející acyl; Molecular Docking Simulation; Humans